Experimental investigation of flow behaviour of open channel flow through a linear straight contraction / Muhammad Izhar Firki Mohd Adenan - Mohd Adenan, Muhammad Izhar Firki (2022)
Water channels are utilized for a assortment of instructive and inquire about purposes counting hydrodynamic and streamlined ponders. In this project, we study the investigation of open channel flow behavior through linear straight contraction. On the test portion, several angles of wall gaps are installed. This will result in a varied water flow for each wall gap. This method we can use in the weirs to slow down the flow of water so that we can minimize the velocity of movement for the fluid. A weir is a small dam that spans a body of water like a river and is able to control flood problems. This objective is to determine the shape and velocity of the water flow. The application used in this experiment is Circulation Water Channel (CWC). The material of the test section is made from transparent acrylic cover. The expected result is that a larger wall gap will reduce water flow velocity. The water flow rate will be influenced by the angle of the wall gap. The larger the angle used, the water flow rate will decrease. At the same time, the resulting water patterns may also be different.